I dream of a journey - Miyakoshi, Akiko, 1982- (Toronto, ON : Kids Can Press, 2020)
The hotelkeeper loves his job, meeting guests from around the world who share stories with him of faraway places. At night, the hotelkeeper dreams of going on a journey to new and wonderful places--wondering if his dreams and longing will ever turn into a real journey.
Translation of: Boku no tabi.
Booklist
Horn Book Guide
Kirkus Review
Publishers Weekly
School Library Journal
Keywords: Hotelkeepers -- Fiction; Imagination -- Fiction; Dreams -- Fiction; Travel -- Fiction; Picture books